Large eddy simulation study of ammonia dilute spray flames under MILD conditions - Zhenhua An; Yanhui Song; Jiangkuan Xing; Ryoichi Kurose (Applications in Energy and Combustion Science)
Liquid ammonia has received increasing attention as a carbon-free fuel due to its potential to reduce the cost and size of power generation equipment. However, its practical application faces significant challenges, primarily related to its low combustion intensity and high NOx emissions. Moderate and intense low-oxygen dilution (MILD) combustion offers a promising approach to enhancing combustion stability while maintaining NOx emissions within acceptable limits. In this study, the flow and spray characteristics, combustion features, and emission performance of ammonia dilute spray flames are numerically investigated using a jet in hot co-flow (JHC) configuration. A range of co-flame temperatures and oxygen contents are considered. The gaseous ammonia jet flame is also studied as a comparison. The results indicate that under the JHC configuration, compared to gaseous ammonia combustion, liquid ammonia combustion reduces the heat release rate (HRR), increases the uniformity of the reaction zone, and reduces NOx emissions. Increasing the co-flame temperature and oxygen content reduces the spray penetration length and has minimal influence on the droplet size distribution. In addition, these changes lead to a transition in the combustion mode from premixed to diffusion. As the temperature and oxygen content increase, the maximum combustion temperature and HRR increase, the flame height decreases, and the lift-off distance is also affected. Moreover, a higher co-flame temperature leads to increased NO emissions but reduced N2O emission, indicating the importance of optimizing the co-flame temperature for effective emission control. Increasing the oxygen content in the co-flame exacerbates NOx emissions, suggesting that a lower oxygen content should be maintained to minimize emissions. The findings of this study provide theoretical insights into the application of liquid ammonia under MILD combustion conditions.